Ethical Leadership Practices and Service Delivery of Public Institutions in Narok County, Kenya - Kinyamal, Ngatuny; Juma , Dennis (Human Resource and Leadership Journal, 2025)
Purpose: The study sought to determine the relationship between ethical leadership practices and service delivery of public institutions in Narok County, Kenya. The specific objectives were to assess the effect of integrity, transparency, fairness in decision-making and accountability practices on service delivery of public institutions in Narok County. Methodology: A descriptive research design was adopted, and data were collected using semi-structured questionnaires A sample of 171 respondents, was calculated using the Yamane’s (1967) formula. Further selection of the participants was done using stratified random sampling technique. Data was analyzed using both descriptive and inferential statistics, including Pearson correlation and multiple linear regression. Findings: The findings revealed that all four dimensions of ethical leadership are positively and significantly associated with service delivery in public institutions. The regression model showed 73.1% of the variation in service delivery can be explained by the combined influence of the four ethical leadership variables. The findings also showed a significant F-statistic (p < 0.05). Unique Contribution to Theory Practice and Policy: The study recommended that: public institutions should institutionalize regular training on ethical behavior, values, and integrity for both leaders and employees and should hold both leaders and staff accountable for service outcomes.